Biological control of the millet head miner Heliocheilus albipunctella in the Sahelian region by augmentative releases of the parasitoid wasp Habrobracon hebetor: effectiveness and farmers perceptions - Ba, Malick N.; Baoua, I.; N'Diaye, M.; Dabiré, C.; Sanon, A.; Tamò, Manuele (Springer, 2013)
On-farm augmentative releases of the parasitoid Habrobracon hebetor (Say) for controlling the millet head miner (MHM) Heliocheilus albipunctella (de Joannis) were tested in Burkina Faso, Mali and Niger from 2007 to 2009. In addition, a survey of farmers’ perceptions of insect pests, with particular focus on MHM, and the biological control program (BCP) was carried out. There was a significant increase of MHM parasitization rate after the releases, with up to 97% mortality. The survey on farmers’ perceptions revealed a fair knowledge of the MHM and the ability of farmers to describe the pest and the damage it caused. Farmers claimed that the biocontrol agent H. hebetor is effective and perceived a significant gain in grain yield due to this control strategy. Implications of these findings for a large extension of the MHM biocontrol program are discussed.